1997
DOI: 10.1038/sj.leu.2400525
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of soluble CD44 standard, but not of variant isoforms v5 and v6, in B cell chronic lymphocytic leukemia

Abstract: The CD44 cell surface proteoglycan participates in a variety of CD44v6 has been also described in high-grade, but not in functions including lymphohematopoiesis, lymphocyte homing low-grade, non-Hodgkin's lymphomas. [25][26][27] and tumor metastasis. In addition to the standard form Upon interaction with its natural ligand, or when ligated by addition to these clinical and biological parameters, serum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 7 publications
2
28
0
Order By: Relevance
“…In CLL, elevated CD44 serum levels and high panCD44 as well as CD44v surface levels have been suggested as prognostic markers. While apparent consensus exists on the association of high CD44 serum levels with poor clinical outcome (17,18,28), the prognostic relevance of panCD44 and CD44v surface levels on circulating CLL cells remains arguable. Our data do not support a prognostic value of high CD44 levels on peripheral blood CLL cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CLL, elevated CD44 serum levels and high panCD44 as well as CD44v surface levels have been suggested as prognostic markers. While apparent consensus exists on the association of high CD44 serum levels with poor clinical outcome (17,18,28), the prognostic relevance of panCD44 and CD44v surface levels on circulating CLL cells remains arguable. Our data do not support a prognostic value of high CD44 levels on peripheral blood CLL cells.…”
Section: Discussionmentioning
confidence: 99%
“…Correlative studies have suggested CD44 as a negative prognostic marker in CLL (17)(18)(19), but the underlying molecular mechanisms are not fully understood. Here, we aimed to examine the role of CD44-HA interactions for CLL cell positioning within lymph node compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Published results 16,43 and our in silico meta-analysis (supplemental Figure 1A and Table 2) support both of these findings. Available reports on surface vs soluble and on CD44s vs CD44v isoforms in CLL 37,[43][44][45][46][47][48][49][50] show in their entirety no clear-cut prognostic associations. However, they implicate a higher CD44 turnover in CLL over normal lymphocytes, especially in more aggressive disease subsets.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear difference between the colorectal carcinoma Astler-Coller's stage B patients group and the colorectal carcinoma Astler-Coller's stage C patients group, although the heterogeneity and the intensity of the bands were greater in the Astler-Coller's stage C patients group. CD44 as a marker of disease progression (Guo et al, 1994;De Rossi et al, 1997;Ristamäki et al, 1998). For instance in ovarian cancer, the concentration of sCD44std was found to be higher and sCD44v5 to be lower than in healthy controls (Zeimer et al, 1997).…”
Section: Purification Of Scd44mentioning
confidence: 99%